Antimicrobial peptides in Dendrobium officinale: Genomic parameters, peptide structures, and gene expression patterns - Huiming Huang; Wen‐Yee Lee; Hui Zou; Haiming Li; Shuhe Zhang; Heping Li; Jiangbo Lin (The Plant Genome, 2023)
Abstract A weak codon usage bias was found in Dendrobium catenatum (D. officiale) antimicrobial peptides (AMPs), after the analysis of relative synonymous codon usage, GC contents, and the effective number of codons. The codon usage preference was mainly influenced by natural selection pressure. The self‐optimized prediction method and SWISS‐MODEL were applied for peptide structural and domain analyses, and some typical antimicrobial domains were found in D. officinale AMP amino sequences, such as knot1 domain, gibberellins‐stimulated domain, cupin_1 domain, defensin_like domain, and SLR1‐BP (S locus‐related glycoprotein 1 binding pollen coat protein) domain. To investigate the AMPs gene expression pattern, abiotic stresses, such as salt stress, drought stress, salicylic acid (SA), and methyl jasmonate (JA), were applied and the gene expression levels were detected by the real‐time fluorescent quantitative polymerase chain reaction. Results showed that, even though the basic AMPs gene expressions were low, some AMPs can still be induced by salt dress, while the drought dress did not show the same impact. The SA and JA signaling pathways might be involved in most of the AMPs expressions. The natural selection of the D. officinale AMPs and thus forming diverse types of AMPs enhanced the plant's innate immunity and disease resistance capability, which would lead to a better understanding of the molecular mechanism for D. officinale adapting to the environment. The finding that salt stress, SA, and JA signaling pathways can induce AMP expression lays a foundation for the further development and functional verification of D. officinale AMPs.